(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In our paper, we propose to focus on the use of video products in the educational process of teacher education in Ukraine.First of all, it is important for us to present a justification of the features and importance of using video projects as part of theoretical material / educational content / online and offline courses. After all, the use of video projects allows to deepen the knowledge of future teachers, including audiovisual involvement in the perception of terminology, complex elements of teacher organization, legislation or other theoretical aspects.Secondly, we believe that it is worth noting and presenting the experience of Ukrainian students of pedagogical specialties' involvement in video projects (in particular, the creation of a social video, etc.). After all, such work allows you to reassess your own skills in using technology, acquire new knowledge, formulate a strategy for implementing project-based learning in secondary school practice, and build strong cause-and-effect relationships between the knowledge and experience of using it through technology and social media.All of this together allows us to observe the formation of a future teacher who is not separated from the challenges of the technology world, but who uses the opportunities of our time in a harmonious and high-quality way.